Effects of Standardized Ileal Digestible Lysine Level on Growth Performance of 80 to 120 lb DNA Grow-Finish Pigs - Rafe Q. Royall; Robert D. Goodband; Mike D. Tokach; Joel M DeRouchey; Jordan T. Gebhardt; Jason C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2021)
The objective of this study was to estimate the SID Lys requirement for growth and feed efficiency of 80- to 120-lb DNA grow-finish pigs. A total of 608 barrows and gilts (600 × 241, DNA; initially 80.2 ± 2.0 lb) were used in two separate studies lasting 14 and 21 d, respectively. Pens of pigs were blocked by BW and randomly allotted to 1 of 6 dietary treatments with 7 to 9 pigs per pen and 12 replications per treatment in a randomized complete block design. Similar number of barrows and gilts were placed in each pen. Dietary treatments were corn-soybean meal-based and formulated to 0.80, 0.88, 0.96, 1.04, 1.12, and 1.20% SID Lys. Increasing SID Lys increased (linear, P = 0.036) the average daily gain (ADG), resulting in pigs fed 1.20% SID Lys having the greatest final body weight. The F/G improved, while lysine intake/d, and lysine intake/kg of gain increased (linear,P<0.001) with increasing SID Lys. Feed cost per pig and feed cost/lb gain increased (linear,P<0.005) with increasing SID Lys. Total revenue per pig tended to increase (linear,P= 0.060) with increasing SID Lys. At low ingredient and pig prices, income over feed cost (IOFC) tended to decrease (linear,P= 0.099) as SID Lys increased. At high ingredient prices, there were no differences in IOFC among dietary treatments. In summary, these results suggest that for 80- to 120-lb DNA growing-finishing pigs, the response to SID lysine was linear to at least 1.20% of the diet. However, based on current ingredient prices, the improved growth performance observed with increasing SID Lys did not offset the added diet costs, suggesting growth performance must be compared with IOFC when deciding optimal levels.
Keywords: amino acid; growth; lysine requirement; grow-finish pig